THE BEGINNING OF SEXUAL RELATIONSHIPS AND DRUGS CONSUMPTION AMONG MELITOPOL YOUNG CITIZEN - Liapunova, V. А.; Zuitnik, Т. S.; Zemskiyi, А. B.; Tsarkova, O.V. (International Journal of Psychosocial Rehabilitation, 2020)
Purpose. The research work is aimed at studying and analyzing the onset of sexual activity and injecting drug use among young people of Melitopol (Zaporizhzhya region), which will make it possible to plan a number of preventive measures in order to prevent deviant behavior. Theoretical basis. The authors focus on the social problems associated with the late informing young people about the possible risks of early sexual relations and the use of drugs. Namely: students, young people, who move to another city or country, thus remaining without parental control. Scientific originality. This study allowed us to see the dynamics of attitudes (2007–2018) to injection drugs of boys and adolescent girls in cities with a population of up to 200 thousand (on the example of Melitopol, Zaporizhia region); track the tendency to awareness and care about your health during early sexual intercourse; plan a number of preventive measures to prevent the above phenomena. Conclusion. Young people between the ages of 13 and 15 put themselves at risk of becoming injecting drug users, getting infected with AIDS virus, Hepatitis B/C: 3,5% of those registered were infected with AIDS virus between the ages of 13 and 18; 28,5% were infected at the age of 18 – 24 years. The consumption of psychoactive substances (surfactants) from the injection form of consumption turned into a form of smoking and taking pills. Priority areas for further research have been identified: to conduct research with an interval of three years; to reach students of higher educational institutions, pupils of city colleges, with the aim of further cooperation with deans of educational institutions for holding lectures, talks, thematic evenings for students on healthy lifestyles, AIDS virus and the dangers of psychoactive substances consumption.